الكلام الانشائي الطلبي في قصيدة البردة الحسنية الحسينية فى مدح أل خير البرية لسيد صالح الجعفري - nur nafiudin (EL- Hayah, 2024)
In the science of rhetoric, constructive speech is speech that does not intend to be truthful or untruthful. It is divided into two parts: on-demand and non-demand. This research investigates the science of meanings, especially in requesting constructional speech. From the above-mentioned data, this research was searching for the poetic compositional speech in the poem Al-Burda Al-Hassaniyyah Al-Husseini in praise of Al-Khair Al-Bariyyah by Sayyid Saleh Al-Jaafari. The type of this research is qualitative research using a library study. The basic data used in this research is the book “The Poem of Burdah Al-Hassaniyyah Al-Hussainiya in Praise of the Good of Al-Bariyyah” by Sayyid Saleh Al-Jaafari. The source of data in this research is from books on rhetoric. The results of this research are as follows: It contains 73 forms of the requesting constructional speech, meaning 29 of the imperative form, with three meanings: guidance, threat, and supplication. Then 12 of the form of prohibition with four meanings: guidance, contempt, threat, and supplication. Then 13 of the interrogative form with four meanings: guidance, information, multiplication, and magnification. Then 5 of the form of wishing with two prohibitions: the hope that cannot be achieved and the hope that may be possible. Then 14 of the form of the call with three meanings: originality, glorification, and supplication.